JUSTIFICATION OF GEOINFORMATION SYSTEM ON LAND SOILS QUALITY MONITORING - Moskalenko, А. А. (Land Management, Cadastre and Land Monitoring, 2012)
In article the making components necessary for for creation of system of geoinformation monitiring of soil and development of conceptual model of complex GIS of a qualitative condition of soil are analyze. Components of bank of geospatial data of monitiring of quality of lands of agricultural purpose are proved.